Research on Noise Reduction of RV Reducers by Gear Modification Based on the Orthogonal Test - Liu Wenchuan; Zhang Yinghui; He Weidong (Jixie chuandong)
In view of the noise generated during the operation of the RV reducers, the tooth surface of the involute gear and the cycloid gear are modified, the modification amount is obtained based on the empirical modification formula, and the orthogonal test table is established. With the RV110E type reducer as the research object, the noise value of the reducer under different modifications is obtained based on the RecurDyn software. The results show that the noise reduction effect of the RV reducer is significant for the involute gear modification, and the maximum noise value is reduced by 7.78 dB(A). The virtual prototype of the RV110E type reducer is built with Romax software, and the parameters of involute gear modification are imported. Comparing the simulation results before and after the modification, it can be seen that the transmission error of the combined modified involute gear is reduced, the peak load per unit length of the tooth surface is reduced, the problem of tooth surface off-load and noise are improved, and the transmission stability of the reducer is effectively improved. The research results have certain reference significance for gear modification of different types of RV reducers.